2020
DOI: 10.1186/s13089-020-00170-x
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for using the velocity–time integral and the minute distance for assessing the stroke volume and cardiac output in point-of-care settings

Abstract: Background: Stroke volume (SV) and cardiac output (CO) are basic hemodynamic parameters which aid in targeting organ perfusion and oxygen delivery in critically ill patients with hemodynamic instability. While there are several methods for obtaining this data, the use of transthoracic echocardiography (TTE) is gaining acceptance among intensivists and emergency physicians. With TTE, there are several points that practitioners should consider to make estimations of the SV/CO as simplest as possible and avoid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 38 publications
1
95
0
1
Order By: Relevance
“…LVOT VTI was recommended as a simple, feasible and reproducible measurement to serially track CO (21). Recent studies have shown that VTI can be used for assessing the effects of some therapeutic interventions on CO, or for performing tests assessing preload responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…LVOT VTI was recommended as a simple, feasible and reproducible measurement to serially track CO (21). Recent studies have shown that VTI can be used for assessing the effects of some therapeutic interventions on CO, or for performing tests assessing preload responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…LVOT cross-sectional area is derived from the LVOT diameter in parasternal long-axis view using the formula π r 2 , and LVOT VTI is obtained by tracing the envelope of the Doppler spectrum of systolic flow in the apical 5-chamber view (Fig. 2) [20]. As the LVOT diameter is constant for a given person, VTI (normal: ∼18–22 cm) is often used as a surrogate for cardiac output changes assuming the heart rate is relatively constant.…”
Section: The Pumpmentioning
confidence: 99%
“…Although ultrasound-guided IVC collapsibility was once believed to be a strong proxy for fluid status, the propensity for measurement variability between providers has caused its usage to decrease [7]. Similarly, although LVOT VTI is a strong representation of a patient's left ventricular systolic function and provides unique insights into prognosis, the burden of manual calculation and potential for user error has left it historically underutilized [8,9]. Top ultrasound manufacturers have begun implementing AI in this setting due to the computational speed and accuracy with which it can auto-calculate these parameters [7].…”
Section: Dear Editormentioning
confidence: 99%